DEPRESSION INTENSIFICATION IN ONCOLOGICAL PATIENTS - Ewa Humeniuk; Olga Dąbska; Aleksandra Krupa (Rozprawy Społeczne)
Introduction The article describes assessment of depression occurrence in cancer patients in relation to the received social support and patients’ lifestyle